Emerging need for meditation practice in the community - S Ganesh Kumar (Wolters Kluwer Medknow Publications, 2014)
Meditation practice is one of the most important health factors that need attention, especially in developing countries including India. This is keeping in view of the recent increase in the trend of non-communicable diseases and their risk factors in the population. The need of the hour is to address the need for practice of meditation at a community level to improve the populace health. This article explains the importance of meditation, its awareness generation, and the factors required to improve its practice in the community.